Stroke syndromes - Caplan, Louis R.; Van Gijn, J. (Cambridge medicine (Series), 2012)
"The first two editions of Stroke Syndromes were widely welcomed as authoritative reference works in the assessment and diagnosis of stroke. This revised and updated third edition remains the definitive guide to patterns and syndromes in stroke. A comprehensive survey of all types of neurological, neurophysiological and other clinical dysfunction due to stroke. The book contains descriptions of clinical problems encountered in stroke patients and their differential diagnosis, enhancing pattern recognition and enabling clinicians to differentiate between possible locations on the basis of symptoms and signs. The companion volume Uncommon Causes of Stroke completes this highly authoritative reference work which clinicians in neurology will find essential to the understanding and diagnosis of stroke"--